A Descriptive-Comparative Study of Fear of Missing Out (FoMO), Social Media Use, and Viral Trend Participation Among Early Adults in Indonesia - Hani Wardah; Rully Afrita Harlianty (Nusantara Journal of Behavioral and Social Science, 2026)
The development of digital technology and social media has contributed to the emergence of Fear of Missing Out (FoMO), a psychological phenomenon in which individuals feel left out of others’ social experiences. This study employed a descriptive-comparative cross-sectional survey design to examine FoMO among early adults in Indonesia. Data were collected through an online questionnaire distributed via Google Forms, involving 400 respondents aged 18–40 years. Accordingly, the sampling approach is convenience sampling, described as voluntary response sampling. The research instrument was a 15-item FoMO scale with high reliability (Cronbach’s Alpha α = .923). The results indicated that 71.5% of respondents reported high levels of FoMO among early adults in Indonesia. Significant differences in FoMO levels were found based on the types of viral trends followed and the number of social media platforms used, particularly among individuals using more than three platforms and engaging with trends such as concerts and merchandise collections. In contrast, no significant differences were observed across demographic variables, including gender, age group, employment status, or geographic location. These findings suggest that FoMO is widely experienced among early adults in Indonesia and is more closely associated with patterns of digital engagement than with demographic characteristics.